2019
DOI: 10.11591/ijict.v8i3.pp122-127
|View full text |Cite
|
Sign up to set email alerts
|

Classifiers ensemble and synthetic minority oversampling techniques for academic performance prediction

Abstract: The increasing need for data driven decision making recently has resulted in the application of data mining in various fields including the educational sector which is referred to as educational data mining. The need for improving the performance of data mining models has also been identified as a gap for future researcher. In Nigeria, higher educational institutions collect various students’ data, but these data are rarely used in any decision or policy making to improve the academic performance of students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To improve students' academic performance, Yusuf A proposed a performance prediction model using stack classifier and composite minority oversampling technology. The research results showed that this technology improved the performance of data mining models [17].…”
Section: Related Workmentioning
confidence: 92%
“…To improve students' academic performance, Yusuf A proposed a performance prediction model using stack classifier and composite minority oversampling technology. The research results showed that this technology improved the performance of data mining models [17].…”
Section: Related Workmentioning
confidence: 92%
“…Machine learning models [14]- [16] such as RF, SVM [17], [18], decision tree, K-nearest-neighbors (KNN) [19], principal component analysis (PCA) [20] are successfully applied in many application areas. We have built up an ensemble model [21], including SVM and XGBoost [22], that gives better precision when contrasted with other individual machine learning models.…”
Section: Literature Surveymentioning
confidence: 99%
“…There are more data of normal wear than initial and sharp wear, that will induce more samples being classified into categories with more samples, resulting in poor generalization of the model. Synthetic Minority Oversampling Technique (SMOTE) is often used for unbalanced data classification [12,20]. The idea is to interpolate samples of the nearest K less-sample categories to form a new category and add it into the data set, so that different categories tend to be more balanced.…”
Section: Unbalanced Data Processingmentioning
confidence: 99%